2011
DOI: 10.1177/1470320311417655
|View full text |Cite
|
Sign up to set email alerts
|

Association between genetic polymorphism of the angiotensin-converting enzyme and diabetic nephropathy: a meta-analysis comprising 26,580 subjects

Abstract: Our study suggested that the ACE I/D polymorphism may contribute to DN development, especially in the Asian group with T2DM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
47
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(53 citation statements)
references
References 89 publications
5
47
0
1
Order By: Relevance
“…Our observations relating to the relationship of ACE polymorphism with diabetic nephropathy were in agreement with other previous studies, a meta-analysis study verified that II genotype has compact the risk of diabetic nephropathy [16]. Our results were also supported by another meta-analysis data, where reported considerable involvement between the ACE DD polymorphism and the possibility of DN [17]. In the same line, several studies in different population have reported that a strong relationship between the ACE DD genotype and the risk for diabetic nephropathy was reported in Malaysian [18], British Caucasian [19], Bahraini [20], Japanese [21], Korean [22], and Americans [14] populations.…”
Section: Discussionsupporting
confidence: 82%
“…Our observations relating to the relationship of ACE polymorphism with diabetic nephropathy were in agreement with other previous studies, a meta-analysis study verified that II genotype has compact the risk of diabetic nephropathy [16]. Our results were also supported by another meta-analysis data, where reported considerable involvement between the ACE DD polymorphism and the possibility of DN [17]. In the same line, several studies in different population have reported that a strong relationship between the ACE DD genotype and the risk for diabetic nephropathy was reported in Malaysian [18], British Caucasian [19], Bahraini [20], Japanese [21], Korean [22], and Americans [14] populations.…”
Section: Discussionsupporting
confidence: 82%
“…Therefore, we suggest that the genetic variation at the ACE locus as D/D variant in intron 16, contribute to an increased risk of nephropathy in T2DM patients, but not extent of DN severity (as the allelic or genotypic distribution was comparable between the two DN groups) in studied population. Our findings were in conformity with other studies [26][27][28][29][30][31] but not all [32,55,56]. This difference may possibly be due to different races, methods of quantitation and patient selection; as proteinuria in adults is a multifactorial condition frequently linked with diabetes, the issue of whether proteinuria is due to diabetes or some other etiology remains debatable, but there was no uncertainty in our group of patients on the role of T2DM in diabetic nephropathy constitution as we excluded the patients who had proteinuria/renal disorders before their diabetes was diagnosed, thus we confined our study to diabetic kidney diseases.…”
Section: Discussionsupporting
confidence: 81%
“…Thus, the contribution of ACE gene polymorphism to the heritable part of risk for diabetic nephropathy seems important, and is supported by findings from published meta-analyses [28,62] along with other studies done among Indians [31,63], Japanese [29], French [64], Egyptian [65] and Taiwan [27] diabetic patients. However, our results do not coincide with studies done among Chinese [66], Tunisian [55], French [56], Turkish [34] and Iranian [67] diabetic cases.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Wang et al performed a meta-analysis of 14,108 DKD cases and 12,472 controls from 63 published studies [75]. When the authors included all ethnicities and both diabetes types, there was a significant association between an ACE insertion/deletion polymorphism and the risk of DKD.…”
Section: Candidate Gene Association Studiesmentioning
confidence: 99%